Diaph1-Deficiency Is Associated With Major T, Nk and Ilc Defects in Humans - Ayaz Güner, Şerife; Azizoglu, Zehra Busra; Babayeva, Royala; Haskologlu, Zehra Sule; Acar, Mustafa Burak; Ayaz-Guner, Serife; Okus, Fatma Zehra; Eken, Ahmet (Springer/plenum Publishers, 2024)
Loss of function mutations in Diaphanous related formin 1 (DIAPH1) are associated with seizures, cortical blindness, and microcephaly syndrome (SCBMS) and are recently linked to combined immunodeficiency. However, the extent of defects in T and innate lymphoid cells (ILCs) remain unexplored. Herein, we characterized the primary T, natural killer (NK) and helper ILCs of six patients carrying two novel loss of function mutation in DIAPH1 and Jurkat cells after DIAPH1 knockdown. Mutations were identified by whole exome sequencing. T-cell immunophenotyping, proliferation, migration, cytokine signaling, survival, and NK cell cytotoxicity were studied via flow cytometry-based assays, confocal microscopy, and real-time qPCR. CD4+ T cell proteome was analyzed by mass spectrometry. p.R351* and p.R322*variants led to a significant reduction in the DIAPH1 mRNA and protein levels. DIAPH1-deficient T cells showed proliferation, activation, as well as TCR-mediated signaling defects. DIAPH1-deficient PBMCs also displayed impaired transwell migration, defective STAT5 phosphorylation in response to IL-2, IL-7 and IL-15. In vitro generation/expansion of Treg cells from na & iuml;ve T cells was significantly reduced. shRNA-mediated silencing of DIAPH1 in Jurkat cells reduced DIAPH1 protein level and inhibited T cell proliferation and IL-2/STAT5 axis. Additionally, NK cells from patients had diminished cytotoxic activity, function and IL-2/STAT5 axis. Lastly, DIAPH1-deficient patients' peripheral blood contained dramatically reduced numbers of all helper ILC subsets. DIAPH1 deficiency results in major functional defects in T, NK cells and helper ILCs underlining the critical role of formin DIAPH1 in the biology of those cell subsets.Graphical AbstractThe summary of findings are presented as a graphical abstract. DIAPH1 deficiency results in multiple defects in CD4+ T, Treg, NK cells and ILCs.
AYAZ GUNER, SERIFE/0000-0002-1052-0961; BASARAN, KEMAL ERDEM/0000-0001-6035-9398; CANATAN, Mehmed Fatih/0000-0002-2844-061X; Can, Salim/0000-0003-3797-3001; Acar, Mustafa Burak/0000-0002-9109-6575
Keywords: DIAPH1; Macrothrombocytopenia; Immunodeficiency; Cytoskeletal defects